Money in the Great Recession did a crash in money growth cause the global slump? - edited by Tim Congdon (Cheltenham Edward Elgar Publishing, 2017)
No issue is more fundamental in contemporary macroeconomics than identifying the causes of the recent Great Recession. The standard view is that the banks were to blame because they took on too much risk, 'went bust' and had to be bailed out by governments. However very few banks actually had losses in excess of their capital. The counter-argument presented in this stimulating new book is that the Great Recession was in fact caused by a collapse in the rate of change of the quantity of money. This was the result of a mistimed and inappropriate tightening of banks' capital regulations, which had vicious deflationary consequences at just the wrong point in the business cycle. Central bankers and financial regulators made serious mistakes. The book's argument echoes that on the causes of the Great Depression made by Milton Friedman and Anna Schwartz in their classic book A Monetary History of the United States.
Includes bibliographical references and index.
Keywords: Money supply